The Resuscitation, Equilibrium and De-escalation (RED) strategy: a phased, personalized hemodynamic support in children with sepsis - Fernández-Sarmiento, Jaime; Ranjit, Sushitra; Sanchez-Pinto, L. Nelson; Nadkarni, Vinay M.; Jabornisky, Roberto; Kissoon, Niranjan (Frontiers in Pediatrics, 2025)
Hemodynamic support in critically ill children with septic shock is a pervasive challenge in the intensive care settings. Cardiovascular involvement in sepsis entails both macro- and microcirculation abnormalities, with the main treatment objectives seeking to increase cardiac output and improve tissue perfusion, respectively. Fluid therapy and vasoactive drugs are cornerstone therapies for circulatory problems in sepsis. Fluid boluses are a common first-line treatment for actual and relative hypovolemia. However, their use has been linked to adverse events due to factors such as their composition, high volumes and rapid infusion rates, and the variable response of individual patients. Furthermore, they often have transient efficacy or lack of response in many patients. Vasoactive drugs are also often used late, which favors repetitive fluid boluses, leading to hypervolemia, tissue edema and worse outcomes. After the resuscitation phase, active fluid removal through diuresis or dialysis is increasingly being used in patients who receive fluid therapy, but it has not yet been standardized, and the safest and most effective strategies in children are still not known. We believe that these interventions for hemodynamic problems in sepsis offer an opportunity to personalize treatment and apply precision medicine strategies. Using a phased approach adapted to each patient's context and clinical condition can potentially improve outcomes. The proposed Resuscitation, Equilibrium and De-escalation (RED) strategy is a simplified phased hemodynamic management approach for patients with sepsis and septic shock. Our goal with the introduction of this concept is to organize and underscore the fact that the cardiovascular support of sepsis is dynamic and should be adapted to each individual and context.